Influência da freqüência cardíaca na qualidade de vida e capacidade física em pacientes com fibrilação atrial crônica - Jaber, Jefferson [UNIFESP] (2008)
Background: Rate control is an acceptable alternative to rhythm control in patients with chronic atrial fibrillation. However, current criteria for rate control are empirical and based on a small amount of scientific data. Objective: This study was designed to analyse the influence of heart rate measured by the 6-minute walk test, 24-hour Holter monitoring and cardiopulmonary exercise test on quality of life and exercise capacity in patients with atrial fibrillation. Methods: Eighty-nine males patients with chronic atrial fibrillation and resting heart rate < 90 bpm were included. These patients underwent a quality of life questionnaire (assessed by Medical Outcomes Study Short Form Health Survey SF-36), 6-minute walk test, cardiopulmonary exercise test and 24-hour Holter monitoring. Results: There was a significant difference on quality of life in physical and mental summary scores in patients with maximal heart rate . 110 bpm on 6-minute walk test in comparison with heart rate > 110 bpm (284.10 } 81.37 vs 247.45 } 85.03, p = 0.04 and 316.59 } 75.91 vs 266.84 } 93.75, p = 0.01, respectively) and in physical summary score in patients with average heart rate . 80 bpm on Holter monitor in comparison with heart rate > 80 bpm (284.25 } 70.91 vs 240.81 } 93.55, p = 0.02). There was no significant difference on quality of life in patients with maximal heart rate between 85 and 115% of the maximum age-predicted heart rate at peak exercise in comparison with peak heart rate > 115% of the maximum age-predicted heart rate. Quality of life was also compared among 3 groups of patients classified by heart rate testing results (Group 1 had heart rate . 110 bpm on 6-minute walk test and . 80 bpm on Holter monitor; Group 2 had heart rate in the target area by one but no both tests; and Group 3 had heart rate > 110 bpm on 6-minute walk test and > 80 bpm on Holter monitor), demonstrating significant difference among 3 groups in physical and mental component summary scores (p = 0.035 e p = 0.026, respectively). Exercise capacity assessment demonstrated that patients with heart rate variation index not over 10 bpm/min showed higher maximal oxygen uptake compared to patients with heart rate variation index > 10 bpm/min (26.76 } 6.17 vs 22.83 } 4.84 ml O2/Kg/min, p = 0.002). Conclusions: Patients with both heart rate . 110 bpm on 6-minute walk test and heart rate . 80 bpm on Holter monitor had better quality of life than patients with higher average heart rates. Holter monitoring and 6-minute walk test shoud be performed as complementary methods to better predict quality of life. The simple heart rate control at rest was not sufficient when we desire to obtain better qualty of life. Better heart rate variation control on cardiopulmonary exercise test was correlated with better exercise capacity in patients with chronic atrial fibrillation.